Income Inequality: A Journey of 200 Years of Economic Thought - Nurkholisoh Ibnu Aman (The Journal of Indonesia Sustainable Development Planning)
The phrase "the rich get richer, and the poor get poorer" encapsulates a phenomenon that has long plagued societies worldwide. Most recently, Riddell et al. (2024) showed that, since 2020, the five richest men in the world have doubled their fortunes. At the same time, almost five billion people have seen their wealth fall. It further argued that corporations and its monopoly power are responsible for driving this unrelenting income inequality. This trend is confirmed by Chen et al. (2019) through an investigation into nearly 1 million firms covering 27 countries. Between 2000 - 2015, there has been a notable increase in corporate market power, especially in advanced economies.